Relasi Kuasa dan Emosi Politik di Media Sosial: Sintesis Psikologi Sosial dan Kajian Wacana - Martahadi, Fahri; Alfalah, Syamsurian (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2025)
Social media has become a central arena of contemporary politics, marked by intensified emotion and the transformation of power relations. This study aims to analyze how political emotions are mediated, produced, and mobilized within power relations on social media through a synthesis of social psychology and discourse studies. The study departs from the assumption that emotions are not merely individual responses, but structured social practices that perform political functions. An interdisciplinary qualitative approach is employed by integrating theories of emotion and power in social psychology with critical discourse analysis. The data consist of political posts and interactions on social media, which are analyzed to identify patterns of emotional expression, discursive strategies, and power dynamics among actors. The findings show that political actors in positions of high power tend to deploy emotions in a controlled manner to construct symbolic legitimacy, while non-elite users express emotions more intensely as a form of articulating dissatisfaction and symbolic resistance. Interactions between these groups generate affective resonance that reinforces online political polarization and conflict. The study also finds that social media platforms play an active role in amplifying specific emotions through algorithmic logics, thereby shaping hierarchies of visibility and the intensity of political emotions. These findings underscore that power relations in digital politics are simultaneously interpersonal, discursive, and technological. This study contributes to the development of digital politics research by offering an integrative analytical framework for understanding political emotions as constitutive elements of power practices on social media.